The Transverse Facial Artery as a Recipient Artery in Neuroplastic Surgery Microvascular Reconstruction - Jude Tunyi, BS; Maria T. Huayllani, MD; Roman Skoracki, MD; Kerry-Ann S. Mitchell, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2022)
Summary:. Microvascular reconstruction in the craniofacial region is particularly challenging due to a paucity of adequate recipient vessels. The facial vessels are commonly utilized; however, in neurocranial reconstruction, the distance from the defect to the vessels may require the use of interposition vein grafts. The superficial temporal vessels, which have the benefit of closer proximity, are often compromised or injured in patients with previous neurosurgical procedures or radiation therapy. Here, we describe the use of the transverse facial artery as a recipient for a latissimus dorsi free flap for scalp reconstruction in a 63-year-old man with a compromised scalp from multiple surgeries and radiation therapy for glioblastoma multiforme. The patient had extensive scarring, temporalis muscle wasting, thinning of the overlying scalp, and notable alopecia. On surveillance imaging, he was found to have an area on the brain concerning for tumor recurrence, for which a surgical biopsy was recommended, with a significant risk of postoperative wound healing complications. We present the use of the transverse facial artery in this case as a recipient artery for free flap reconstruction of the scalp.